Mapping continental Ecuadorian ant species - Fernanda Salazar; Fabian Reyes-Bueno; Daniel Sanmartin; David A Donoso (Sociobiology, 2015)
Ecuador is considered a megadiverse country but information on the distribution and conservation of its ant species is scarce and scattered through the literature. Here we review 150 years of published literature to assemble the first comprehensive species list of continental Ecuadorian ants (excluding the Galapagos Islands). Our main goals are to provide support to online tools (www.theantsofecuador.com), and to serve as a reference to the various research initiatives currently being done in the country. We found 2,124 ant records, from 679 ant species, in 180 localities, reported in 149 articles. We used a subset of this database (i.e. 1,111 records left after removal of duplicates and records with no locality info) to review the Ecuadorian regions, provinces, and national parks covered by the list. For a tropical country, both the number of records per ant species (mean=1.8, SD=1.9) and the number of ant species per locality (mean=6.2, SD=29.7) are extremely low. Moreover, the ant records in our list are biased towards three provinces (Orellana, 410 ant records and 378 ant spp.; Sucumbios, 212 and 177; Pichincha, 129 and 92), one region (Oriente, 779 records and 487 ant species) and non-protected areas (777 ant records and 510 ant spp.). Endemic ants are poorly covered by the Ecuadorian system of protected areas. This study highlights the gaps and opportunities in ant research for the country.